Perancangan Sistem Pengaturan Suhu Ruangan Otomatis Berbasis Mikrokontroler - Partamayasa, I Wayan Gede; Gede Suhartana, I Ketut; Supriana, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 1 (2019): JELIKU Volume 8 No 1, Agustus 2019DO - 10.24843/JLK.2019.v08.i01.p12, 2019)
A server room is a room that is used to store servers, network communication devices such as routers and switches, and other operational related devices. Server rooms that have high temperatures and humidity will affect the performance of all devices, so the temperature and humidity of the server room must be maintained so that the device is not easily damaged. So from that, the company needs to implement a standard to protect the performance of the devices stored in it. To overcome this problem a device was developed that can automatically control and monitor temperature and humidity. The system will be built using temperature and humidity sensors that are used to monitor the temperature of the room, the condition of the room temperature and humidity of the room will be displayed through a website that can be accessed through the internet network.